Strenghening Citizen Oversight in Electoral Politics in Kenya: Evidence from South Rift, Kenya. - (:unkn) unknown (My University, 2013)
Journée d'études LAM-UPPA avec l'IFRA Nairobi, Session Legal Aspects from a Multidisciplinary Perspective
Keywords: African Research